PENGARUH METODE TEAMS GAMES TOURNAMENT DAN MOTIVASI SECARA BERSAMA-SAMA TERHADAP HASIL BELAJAR FIQH SISWA DI MTS NEGERI GOWA - Junaidin Junaidin; Andi Hardianti Maulinda (Fitrah, 2020)
This study aims to determine and describe the effect of the Teams Games Tournament Method and Motivation Together on Students' Fiqh Learning Outcomes at Mts Negeri Gowa. The approach used in this research is a quantitative approach. The results of this study indicate that there is an effect of the Teams Games Method Application (x1) and learning motivation (x2) on learning outcomes (y) at Mts Negeri Gowa, Bontomarannu District, Gowa Regency.